(C3N2H5)3Sb2I9 and (C3N2H5)3Bi2I9: ferroelastic lead-free hybrid perovskite-like materials as potential semiconducting absorbers. Issue 5 (12th January 2022) - Szklarz, Przemysław; Jakubas, Ryszard; Medycki, Wojciech; Gągor, Anna; Cichos, Jakub; Karbowiak, Mirosław; Bator, Grażyna
Abstract : Novel lead-free ferroelastic materials, (C 3 N 2 H 5 ) 3 Sb 2 I 9 and (C 3 N 2 H 5 ) 3 Bi 2 I 9, exhibit rich sequences of phase transitions and reveal semiconducting properties. Abstract : We have synthesised and characterised novel organic–inorganic hybrid crystals: (C 3 N 2 H 5 ) 3 Sb 2 I 9 and (C 3 N 2 H 5 ) 3 Bi 2 I 9 (PSI and PBI ). The thermal DSC and TG analyses indicate four structural phase transitions (PTs) at 366.2/366.8, 274.6/275.4, 233.3/233.3 and 142.8/143.1 K (on cooling/heating) for PSI and two reversible PTs at 365.2/370.8 and 252.6/257.9 K for PBI . Both analogues crystallize at room temperature in the orthorhombic Cmcm structure, which transforms, in the case of PBI, to monoclinic P 21 / n at low temperature. According to the X-ray diffraction results, the anionic component is discrete and built of face-sharing bioctahedra, [M2 I9 ] 3−, in both compounds, whereas cations exhibit distinct dynamical disorder over high temperature phases. Dielectric spectroscopy and 1 H NMR spectroscopy have been used to characterise the dynamical state of the C3 N2 H5 + cations. The ferroelastic domain structure has been characterised by observations under a polarized optical microscope. Both compounds are semiconductors with narrow bandgaps of 1.97 eV (PBI ) and 2.10 eV (PSI ).